REGENERATION STRATEGIES OF PALMS (ARECACEAE) IN RESPONSE TO CYCLONIC DISTURBANCES - DIAN LATIFAH; ROBERT A. CONGDON; JOSEPH A. HOLTUM (Reinwardtia, 2016)
LATIFAH, D., CONGDON, R. A. & HOLTUM, J. A. 2016. Regeneration strategies of palms (Arecaceae) in response to cyclonic disturbances. Reinwardtia 15 (1): 43 ? 59. — Tropical cyclones may act as important ecological drivers in northern Australia including north Queensland, as several cyclones impact this region each year between November and May. Extensive research has been conducted to investigate how regeneration of rainforest plant communities respond to frequent cyclonic disturbances. However, there have been few such studies on palms although they are important components of many rainforests. This research aimed to investigate the effects of canopy gaps following cyclonic disturbance (case study: Cyclone Larry) on regeneration of Arenga australasica (H. Wendl. & Drude) S. T. Blake ex H. E. Moore, Calamus australis Mart., C. moti F. M. Bailey, Hydriastele wendlandiana (F. Muell.) H. Wendl. & Drude and Licuala ramsayi var. ramsayi (F. Muell.) H. Wendl. & Drude. The field research was carried out at five sites in three areas located in northern Queensland: Tam O’Shanter/Djiru National Park, Clump Mountain National Park and Kurrimine Beach Conservation Park. Observations were made of recruitment, growth rate, leaf turnover and life history. We found that responses of palm regeneration following cyclonic disturbance varied among study sites; however, the recruitment of several species was favoured in gaps created by cyclones. The results also provide information on the various stages in the life cycle of the study palms.